Em viagem: o proceso de composição de romances de Mia Couto - Brito, Daniela de [UNESP] (2014)
The main goal of this thesis is to investigate the novels A varanda do frangipani, Um rio chamado tempo, uma casa chamada terra and O outro pé da sereia, written by the Mozambican writer, Mia Couto. The novels were published, respectively, on 1996, 2002 and 2006.The intention is to make clear that the composition process of these literary works is closely bound to the narrative structure mobility and language, verifying, as well, how these movements are interconnected to the identity issue. In order to do so, it is built an itinerary directed to transit spaces, mainly the sea and river, but also journeys made possible in different ways, through dreams, death and memories, focusing, afterwards, on a journey that goes beyond the others: the story telling as a way of mobility highlighted in the novels, outlined as a possibility of displacement via imagery. Following its path, this thesis seeks to address the presence of identity flows, emphasizing the relations established among races; drawing its attention to the foreign characters configuration as well as to the ones who are originally from the country, even though they are seen as foreigners by their countrymen; it follows the learning pathway experienced by the characters in face of the approximation of the young and the old people. Towards the end of the track, this study still goes through the paths of oral expression amalgamated with the writing process, passing through the ways of telling visualized in the novels, moving, therefore, around the narrators and their peculiarities; through the construction mechanisms of the novels, with emphasis on the insertion of a story within another; on the linguistic resources the author serves himself, as in the case of the neologisms and proverbs mobilization, clichés, idiomatic expressions, indicating a language in transit as well, contributing to reassure the idea that, in the analyzed novels, everything is on the move...